The Relationship Between The Role of The Teacher and The Dental and Oral Hygiene Status of Children With Special Needs in SLB Bukesra Ulee Kareng Banda Aceh - Keumala, Cut Ratna; Sisca Mardelita; Putri Awalina; Cut Lieddya Rahmita (Journal Dental Health, 2022)
Children with special needs are special characteristics that are different without always showing mental, emotional or physical disabilities. Teachers are the best promoters of educational activities because they are familiar with the methods of educating and motivating school students. Based on the initial examination of the dental and oral hygiene of students at SLB Bukesra Ulee Kareng Banda Aceh, the results obtained were from 10 children examined; it was known that 6 children had moderate criteria with an average of 2.3, and 4 of them had poor criteria with an average of 4.1. This research is analytic with a cross-sectional design. The population in this study were all teachers and students as subjects. Determination of the sample in the study using a saturated sample technique are 20 teachers and 43 students. The research was carried out at the Bukesra Special School Ulee Kareng Banda Aceh on May 24, 2021. The instruments used in this study were questionnaire sheets, diagnostic sets, and OHI-S KSP sheets. The results showed that the teacher's role as a motivator and educator was not good enough to show poor oral and dental hygiene experienced by 8 respondents (61.5%). Statistical test results obtained, p. Value 0.01. Based on the results of the study, it can be concluded that there is a significant relationship between motivators and educators regarding the dental and oral hygiene of children with special needs. It is hoped that the teacher will further improve in motivating students towards a better direction and carry out good education and in accordance with the child's condition, in explaining the maintenance of dental and oral hygiene.